Supply Chain Structure of Gedong Mango in Jatigede District, Sumedang Regency, West Java - Pardian, Pandi; Renaldi, Eddy; Noor, Trisna Insan; Tridakusumah, Ahmad Choibar; Supyandi, Dika; Heryanto, Mahra Arari (Universitas Galuh, 2024)
District Jatigede is the center of production of mango gedong gincu, the bigst in the Regency of Sumedang. Mango gedong gincu is unique because it has a little red color between the color yellow dominant. Although District Jatigede is one center of production of mango gedong in the Regency Sumedang, it is the second bigst production of mango gedong at the province Level after Regency Indramayu based on 2021 data. Even so, it has yet to be widely known by consumers or people. Hence, the chain supply of mango gedong is interesting to study. This case study uses an analysis structure chain supply to see the flow of products, information, and money linked to commodities mango gedong. Actor tracing in this study approaches the rapid market appraisal method. This study shows four supply chain structures; generally, the chain supplies mango gedong in the Regency Sumedang were sold to local collectors to sell to the big collectors in the Regency of Majalengka or Cirebon. That is due to the center city Majalengka and Cirebon's proximity to District Jatigede compared to Sumedang city center. Apart from that, there are packing houses in Majalengka and Cirebon that are also representative.